The impact of a multimedia-based program on developing the skills of students of the Institute of Fine Arts in Arabic calligraphy (Journal of the College of Basic Education, 2022)
The present research aims at identifying (the Effect of a multimedia-based program in developing the students' skills in the Arabic calligraphy). To achieve the goal, the researchers put the hypothesis of research:1- The first zero hypothesis: There is no statistically significant difference between the mean scores of the experimental group using the multimedia and the control group which is taught according to the normal method in the Arabic calligraphy at the level of significance (05, 0) in the post-cognitive test.2- Second Zero Hypothesis: There is no statistically significant difference between the mean scores of the experimental group using the multimedia and the control group which is taught according to the normal method in the Arabic calligraphy (the patch) at the level of significance (05, 0) in the skill test Post. The research community was represented by the students of the second stage of the Fine Arts Institutes. The Institute of Fine Arts in Kadhimiya was chosen randomly to be a sample of the research. A (25) students were selected as experimental group and (B) 25) students also to be a control group. Students were given a multimedia program in Arabic. The research tools adopted by the researchers are a cognitive achievement test, and a list of skills of the line of the patch, has been confirmed their honesty and persistence. After conducting the cognitive and skill tests on the students (the research sample) and analyzing the results and processing them statistically, it was found that the statistical results are statistically significant. The researchers reached the following conclusions:1. A multimedia-based program has led to a clear development in the skills of students, both cognitively and skillfully.2. The multimedia-based program is superior to the traditional way of developing students' skills in a cognitive and skillful manner.3 - Students showed a great interaction with the multimedia program for what it represents . The recommendations and Suggestions for research were:Recommendations:1 - Include the skills of calligraphy reached by the study in the curriculum of the line of the second grade in the institutes of fine arts.2 - Urge teachers to use multimedia to teach Arabic calligraphy.3 - Training teachers in the preparation of educational software along with the textbook.Suggestions :1 - Studies involving the inclusion of multimedia in other art education materials.2 - Conduct a comparative study of the use of multimedia between Iraq and Saudi Arabia.